The Contribution of the Missionary Schools in Beirut to the Formation of Lebanese Thought - Danis, Mehmet Fahri; Danacioglu, Esra (ILEM, 2023)
New nation-states established in the Middle East after World War I under the mandates of European states generally connect the origins of their national communities with ancient ancestors in order to ground and legitimize their unique existence. The founding myths used in these linking processes function to distinguish the territorial characters of nation-states from other identities and to strengthen the unique existence of these nation-states. The Lebanese thought also gains meaning around such a founding myth and the raison d'etre of the modern Lebanese state is read in the context of Lebanon being free from the Arab-Islamic character around it and having an exceptional culture based on Phoenicianism. One of the most influential actors in the formation of this exceptional character, which Lebanon has through its matching with Phoenicia, is the missionaries in Beirut. In this study, the contribution of Jesuit and Protestant missionaries in Bilad-i Sam to the Phoenician myth of the founding of Lebanon, and on this occasion to the idea of Lebanon, will be emphasized.
Keywords: Lebanon; Phoenician myth; missionary; Jesuits; Protestant missionaries; EDUCATION; Social Sciences - Other Topics